Enhancing women's economic independence through ecological products, ecoenzymes, digital gardens, and sustainable product management based on local wisdom - Efa Wakhidatus Solikhah; Riky Dwi Puriyanto; Deasy Vanda Pertiwi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
This Community Service Program aims to strengthen the economic independence of environmentally conscious women through ecological crafts, eco-enzyme products, digital gardens, and sustainable product management based on local wisdom. The program was carried out with the Environmental Care Women’s Groups in Patalan and Srihardono Hamlets, Bantul, whose members mostly housewives initially had limited skills in ecoprinting, digital gardening, and online marketing. Activities included training and mentoring on ecoprint production using local natural materials, household-scale digital garden development, eco-enzyme liquid soap processing, and digital marketing strategies. A participatory approach ensured active involvement in planning, practice, and evaluation. The results showed significant skill improvement: 80% of participants produced marketable ecoprint products, and 75% successfully promoted their products through social media and simple online stores. Participants also created various ecological products and began managing organic digital gardens. The program increased women’s technical capacities and strengthened their awareness of sustainability and local wisdom. Overall, it effectively supported women’s economic independence while fostering environmental conservation